The Influence of the Team Game Tournament (TGT) Learning Model on Student Learning Outcomes in Thematic Learning in Grade VI at SD Baiturrohman Griya Mangli Indah Jember - Ulfatun Hasanah; Nailul Izzah (IJIE International Journal of Islamic Education, 2023)
This research aims to improve students' learning outcomes through the Team Games Tournament (TGT) learning model in the sixth grade of thematic learning at SD Baiturrohman GMI Jember. The results obtained from the research show that the cooperative learning model, specifically the Team Games Tournament (TGT), can enhance students' learning outcomes. In the first cycle, students' learning outcomes were categorized as follows: excellent (10.5%), good (26.4%), less good (52.6%), and not good (10.5%). In the second cycle, the number of students actively achieving excellent results increased to 31.6%, good results to 57.9%, less good results to 10.5%, and there were no students categorized as not good.